2007
DOI: 10.1002/ajim.20482
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use among immigrant Latino farmworkers in North Carolina

Abstract: There is substantial variation in alcohol use among Latino farmworkers. Although a substantial proportion of farmworkers abstain from alcohol, an equally substantial proportion report alcohol use that poses significant risk for injury on and off the job. More research is needed to document the potential threat to Latino farmworkers by their alcohol use. Interventions targeting alcohol are needed to minimize the risk of injury in an already dangerous occupation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 33 publications
7
47
1
Order By: Relevance
“…Eight studies were found that measured alcohol use by amount and/or frequency among agricultural workers (Ford, King, Nerenberg, & Rojo, 2001;Grzywacz et al, 2006;Grzywacz, Quandt, Isom, & Arcury, 2007;McCurdy, Samuels, Carroll, Beaumont, & Morrin, 2003;Mines, Mullenax, & Saca, 2001;Villarejo, 2000;Winkleby et al, 2006;Winkleby, Snider, Davis, Jennings, & Ahn, 2003), and an additional study compared agricultural workers with urban day laborers (Ritieni, Quesada, Gilbreath, & Kral, 2007). Two other studies included day laborers either exclusively (Organista & Kubo, 2005) or as part of a broader urban population (Fiorentino, Berger, & Ramirez, 2007).…”
Section: Quantity and Frequency Of Alcohol Usementioning
confidence: 97%
“…Eight studies were found that measured alcohol use by amount and/or frequency among agricultural workers (Ford, King, Nerenberg, & Rojo, 2001;Grzywacz et al, 2006;Grzywacz, Quandt, Isom, & Arcury, 2007;McCurdy, Samuels, Carroll, Beaumont, & Morrin, 2003;Mines, Mullenax, & Saca, 2001;Villarejo, 2000;Winkleby et al, 2006;Winkleby, Snider, Davis, Jennings, & Ahn, 2003), and an additional study compared agricultural workers with urban day laborers (Ritieni, Quesada, Gilbreath, & Kral, 2007). Two other studies included day laborers either exclusively (Organista & Kubo, 2005) or as part of a broader urban population (Fiorentino, Berger, & Ramirez, 2007).…”
Section: Quantity and Frequency Of Alcohol Usementioning
confidence: 97%
“…Heavy alcohol use among Latino farm workers is believed to be common, but it remains poorly documented (Grzywacz, Quandt, Isom, & Arcury, 2007). Heavy alcohol consumption increases risk of violence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Evidence for the relationship between alcohol use and farm injuries has been seen in the U.S. [Zhou and Roseman, 1994;Lyman et al, 1999;Stallones and Xiang, 2003;Grzywacz et al, 2007], but we found little such research outside the U.S. [Berry et al, 2007]. Reducing the burden of disease attributable to alcohol consumption has been identified as a priority area by the World Health Organization (WHO) [World Health Organization, 2007].…”
mentioning
confidence: 94%